The Influence of Work Discipline and Work-Life Balance on Employee Productivity at Aston Batam Hotel & Residence - Akmal Rismaulana; Hermansyah (Pt. Threeple Herphi Educate, 2025)
This study investigates the effect of work discipline and work-life balance on employee productivity within the hospitality industry, specifically at Aston Batam Hotel & Residence. Employing a quantitative, causal-associative design, data were collected from 102 employees using structured questionnaires and analyzed through multiple linear regression. The findings reveal that both work discipline and work-life balance exert a statistically significant and positive influence on employee productivity (p < 0.001). Furthermore, the model explains 71.9% of the variance in productivity, indicating a substantial combined effect. The results underscore the importance of structured discipline management and balanced work-life practices in enhancing performance outcomes in hotel operations. Practical implications include the need for reinforced supervision, flexible scheduling, and employee well-being programs to foster sustainable productivity improvements